2020
DOI: 10.1186/s12931-020-01563-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of polycyclic aromatic hydrocarbons in air pollution-induced non-malignant respiratory diseases

Abstract: Epidemiological studies have found strong associations between air pollution and respiratory effects including development and/or exacerbation of asthma and chronic obstructive pulmonary disease (COPD) as well as increased occurrence of respiratory infections and lung cancer. It has become increasingly clear that also polycyclic aromatic hydrocarbons (PAHs) may affect processes linked to non-malignant diseases in the airways. The aim of the present paper was to review epidemiological studies on associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 150 publications
(245 reference statements)
2
70
0
2
Order By: Relevance
“…Humans are exposed directly to PAHs and PAH derivatives or through bioaccumulation in the food chain [7,18,27]. PAHs are known or suspected to be mutagenic, carcinogenic and teratogenic, yet, toxicity between PAHs and their derivatives varies and depends on concentration, time and route of the exposure [7,25,30]. There are legislation and regulations for PAHs in the EU and separate countries [7,25].…”
Section: Pahsmentioning
confidence: 99%
See 3 more Smart Citations
“…Humans are exposed directly to PAHs and PAH derivatives or through bioaccumulation in the food chain [7,18,27]. PAHs are known or suspected to be mutagenic, carcinogenic and teratogenic, yet, toxicity between PAHs and their derivatives varies and depends on concentration, time and route of the exposure [7,25,30]. There are legislation and regulations for PAHs in the EU and separate countries [7,25].…”
Section: Pahsmentioning
confidence: 99%
“…According to epidemiological studies, there is an association between exposure to PAHs, concentrations of air pollutants and the development of allergic and non-allergic asthma, increased symptoms of asthma, risk of asthma exacerbations and lung function decrease, yet according to current data there is a low level of evidence. The strongest evidence is shown for the association between development of asthma and lung function in children [18,27,30,31]. Various mechanisms are likely to play a role in these pathophysiological processes including inflammation, immunoglobulin E (IgE), mast cells' and eosinophils' mediated reactions, oxidative stress, and epithelial and endothelial dysfunction [18,27,32,33].…”
Section: Pahsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not collect chemical composition data of PM 2.5 such as polycyclic aromatic hydrocarbons or heavy metals in this study. However, it is suggested that PAHs or heavy metals in PM 2.5 may have a positive association with development of COPD [ 42 , 43 ]. We recommended that follow-up studies could further analyze the impact of PM 2.5 components on COPD to understand the mechanisms of PM 2.5 on COPD.…”
Section: Discussionmentioning
confidence: 99%